Alternative routes to the institutionalisation of social transfers in sub-Saharan Africa: Political survival strategies and transnational policy coalitions. (October 2021) - Lavers, Tom; Hickey, Sam
Highlights: The paper tests a new framework for explaining social transfers through analysis of eight sub-Saharan African countries. The paper examines the 'institutionalization' of social transfers, and offers a new index for assessing this. Social transfer institutionalization results from political survival strategies and transnational policy coalitions. Either policy coalitions steer governments towards adoption, before competitive elections drive institutionalisation. Or elites respond to perceived distributional crises, augmented by external support. Abstract: The new phase of social protection expansion in the global south remains poorly understood. Current interpretations of the spread of social transfers in sub-Saharan Africa tend to emphasize the influence of elections and donor pressure, often by drawing correlations from statistical data, and focusing on the moment of programme adoption. This study adopts a different approach that traces the actual process through which countries have not just adopted but institutionalized social transfers. We test a new theoretical framework through within and cross-case analysis of the degree to which social protection programmes have become institutionalized in eight African countries. Two main pathways emerge: the first confirms the sense that both donors and elections matter, but goes further in showing the particular ways in which these drivers combine. In particular, transnational policy coalitions tend to play a leading role in adoption, whereas governments pursue the further institutionalization of social transfers as a top-down response to competitive elections. However, we also identify an alternative pathway that involves electorally uncompetitive countries; here, the primary motivation is not elections but elite perceptions of vulnerability in the face of distributional crises, augmented by ideas and resources from transnational policy coalitions. Consequently, the latest phase of social transfer development results from the interplay of political survival strategies and transnational policy coalitions.